INTEGRATED MANAGEMENT SYSTEMS AS A TOOL FOR DEEPENING EUROPEAN INTEGRATION PROCESSES (Economic journal of Lesya Ukrainka Volyn National University, 2021)
Introduction. The application of modern management models, which include integrated management systems based on international standards, is one of the ways to integrate Ukraine into the European space, a relevant area of research. At the same time, the relevance of the formation of integrated management systems as a tool of European integration is determined by the need to ensure balanced, harmonious development, achieving positive stability, competitiveness and security.The purpose of the article. The purpose of the study is to substantiate the theoretical and methodological foundations of the formation of integrated management systems.Results. The existing approaches to the interpretation of the essence of integrated management systems are considered, the preconditions of formation, mission, purpose, principles, criteria of formation of integrated management systems are determined.  It is established that the complexity and versatility of modern problems requires the formation of new integrated management systems. It is substantiated that the main advantages of applying the integration approach over the existing ones are the possibility of considering objects as complex socio-ecological economic systems, and integrated management systems should be aimed at optimizing interdependent economic, social, technological and natural processes in a single environment.It is proposed to consider the integrated management system as a dynamic socially and ecologically oriented model of social development regulation aimed at implementing the principles and provisions of sustainable development implemented in the system of national and international standards, conventions, rules and recommendations by combining efforts of public authorities, local governments civil society, business.Conclusiоns. Integrated management systems are a tool for implementing international standards and EU requirements to ensure an acceptable quality of the environment, living standards, human development, personal security and national security. This necessitates their application for micro-, meso-, macro-level objects, territorial communities, separate territorial systems, implementation in the system of public management and public administration while ensuring the integrity of the object of study and the object of managerial influence.
Keywords: European integration processes, integrated management systems, sustainable development, international standards.